Tracheal Tube-Mounted Camera Assisted Intubation vs. Videolaryngoscopy in Expected Difficult Airway: A Prospective, Randomized Trial (VivaOP Trial) - Grensemann, Jörn; Möhlenkamp, Emma; Breitfeld, Philipp; Tariparast, Pischtaz A.; Peters, Tanja; Punke, Mark A.; Kluge, Stefan; Petzoldt, Martin (Frontiers in Medicine, 2021)
Background Tracheal intubation in patients with an expected difficult airway may be facilitated by videolaryngoscopy (VL). The VL viewing axis angle is specified by the blade shape and visualization of the larynx may fail if the angle does not meet patient’s anatomy. A tube with an integrated camera at its tip (VST, VivaSight-SL) may be advantageous due to its adjustable viewing axis by means of angulating an included stylet. Methods With ethics approval, we studied the VST versus VL in a prospective non-inferiority trial using end tidal oxygen fractions (etO2) after intubation, first-attempt success rates (FAS), visualization assessed by the percentage of glottis opening scale (POGO), and time to intubation (TTI) as outcome parameters. Results 48 patients with a predicted difficult airway were randomized 1:1 to intubation with VST or VL. Concerning oxygenation, the VST was non-inferior to VL with etO2 of 0.79 ± 0.08 (95% confidence intervals: 0.75 to 0.82) vs. 0.81 ± 0.06 (0.79 to 0.84) for the VL group, mean difference 0.02 (-0.07 to 0.02), p=0.234. FAS was 79% for VST and 88% for VL (p=0.449). POGO was 89 ± 21% in the VST-group and 60 ± 36% in the VL group, p=0.002. TTI was 100 ± 57s in the VST group and 68 ± 65s in the VL group (p=0.079). TTI with one attempt was 84 ± 31s vs 49 ± 14s, p<0.001. Conclusion In patients with difficult airways, tracheal intubation with the VST is feasible without negative impact on oxygenation, improves visualization but prolongs intubation. The VST deserves further study to identify patients that might benefit from intubation with VST.